DSS using AHP in Selection of Lecturer - Adriyendi Adriyendi; Yeni Melia (Institute of Advanced Engineering and Science, 2015)
This paper was conducted to apply Analytical Hierarcy Process (AHP), applied as Decision Support System (DSS) model in selection of lecturer at STAIN Batsangkar. Data collected by through observation and interview done in shares of administration academic data center at college. Here in data analyzed to learn the pattern from method used and added with the reference from literature. Experiment done using Microsoft Excel and Expert Choice Software, known that method can yield the optimal decision in selection of lecturer. There by the method recommended to be applied to getting optimal result in decision making.